Ultraearly Intravenous Thrombolysis for Acute Ischemic Stroke in Mobile Stroke Unit and Hospital Settings - Tsivgoulis, Georgios; Geisler, Frederik; Katsanos, Aristeidis H; Kõrv, Janika; Kunz, Alexander; Mikulik, Robert; Rozanski, Michal; Wendt, Matthias; Audebert, Heinrich J (Stroke, 2018)
Background and Purpose- Mobile stroke units (MSUs) are known to increase the proportion of acute ischemic stroke (AIS) patients treated with intravenous thrombolysis (IVT) in the first golden hour (GH) after onset compared with hospital settings (HS). However, because of the low number of AIS patients treated with intravenous thrombolysis within this ultraearly time window in conventional care, characteristics, and outcome of this subgroup of AIS patients have not been compared between MSU and HS. Methods- MSU-GH patients were selected from the Berlin-based MSU (STEMO [Stroke Emergency Mobile]), whereas HS-GH patients were selected from the SITS-EAST (Safe Implementation of Treatments in Stroke-East) registry. The outcome events of interest included the rates of favorable functional outcome (modified Rankin Scale scores of 0 or 1), distribution of the modified Rankin Scale scores, and mortality after 3 months between MSU-GH and HS-GH groups. Results- We identified 117 MSU-GH (38.4% of 305 MSU-treated patients) and 136 HS-GH (0.9% of 15 591 HS-treated patients) eligible patients without prestroke disability. No significant differences were documented in the rates of favorable functional outcome (51.3% versus 46.2%, P=0.487) and mortality (7.7% versus 9.9%, P=0.576) at 3 months, or in the distribution of 3-month modified Rankin Scale scores between the 2 groups ( P=0.196). In multivariable logistic regression analyses, adjusting for potential confounders, MSU treatment was not associated with a significantly different likelihood of favorable functional outcome (odds ratio, 1.84 for MSU patients; 95% CI, 0.86-3.96) or mortality (odds ratio, 0.95; 95% CI, 0.28-3.20) at 3 months. Conclusions- There is no evidence that safety and efficacy of ultraearly intravenous thrombolysis for AIS differs when used in MSUs or in HS.
Keywords: Brain Ischemia; Time-to-Treatment; lidé; Hospitalization; výsledek terapie; Middle Aged; intracranial hemorrhages; Female; Stroke; trombolytická terapie; čas zasáhnout při rozvinutí nemoci; Humans; thrombolytic therapy; mobilní zdravotnické jednotky; ischemie mozku; cévní mozková příhoda; lidé středního věku; kohortové studie; Cohort Studies; mužské pohlaví; hospitalizace; Mobile Health Units; intravenózní podání; ženské pohlaví; Administration, Intravenous; reperfusion; Aged, 80 and over; Treatment Outcome; senioři nad 80 let; Male; Aged; Thrombolytic Therapy; stroke, acute; senioři